Acute necrotizing encephalopathy of childhood: a severe case with fatal outcome - Lee, Yee Lin; Abu Hassan, Hasyma; Ismail, Intan Hakimah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Acute necrotizing encephalopathy of childhood (ANEC) is a rare condition which is important for clinicians to recognize as it has a high mortality rate and can result in significant neurological morbidities. It presents as acute encephalopathy with radiological findings of symmetrical brain lesions in bilateral thalami, putamen, brain stem tegmentum, internal capsule, periventricular white matter and cerebellar medulla. Intravenous methylprednisolone is the mainstay of treatment. Immunoglobulin therapy and therapeutic hypothermia may be used as adjunctive therapy in cases with severe clinical and neuroradiological presentation. We present a case of severe ANEC and discuss the clinical manifestations, neuroimaging and management options.